PENGGUNAAN PUPUK KOMPOS DAN PGPR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN CABAI RAWIT(Capsicum frutescens L.) VARIETAS DEWATA 43 F1 - Jena, Salvatriks Anastasia; karamina, Hidayati; Agastya, I Made Indra (Jurnal Ilmiah Hijau Cendekia, 2024)
The obstacle in producing cayenne pepper plants is the decreasing level of soil fertility caused by the continuous use of inorganic fertilizers, decreased agricultural land productivity and environmental pollution. To overcome these obstacles, efforts can be made to increase the yield of cayenne pepper plants, namely by improving cultivation techniques through fertilizing with organic fertilizers such as cow compost and PGPR. The aim of this research is to determine the effectiveness and best dose of compost and PGPR fertilizer application on cayenne pepper plants. The research started from October to December 2023, and was carried out on community land in Landungsari Village, Lowokwaru District, Malang Regency, East Java Province, with an altitude of Â± 540-700 meters above sea level. The research was carried out using Factorial RAK with two factors and 3 replications. Factor 1, namely cow dung compost which consists of 3 levels: 0; 7.5; and 10 tonnes/ha. Factor 2, namely PGPR consists of 3 levels: 0; 300; and 450 ml/tan. The parameters observed were plant height, flowering age, number of fruit per plant, weight of fruit per plant, production yield and disease resistance. The results of the research showed that there was an interaction between the treatment of cow compost 10 tonnes/ha and PGPR 450 ml/tan on the observation parameters of plant height aged 7, 14 and 28 dap, number of fruit and weight of the second harvest at 77 dap, and disease attacks. The best dose was found in the K2P2 treatment (Compost 10 tonnes/ha + PGPR 450 ml/plant), with plant height of 26.23 cm, flowering age of 34.33 DAP, number of fruit of 70.53, fruit weight of 67. 27 grams and production of 2,415 tons/ha. Diseases that attack cayenne pepper plants are leaf curl and fusarium wilt. Giving PGPR 450 ml/tan can suppress leaf curl disease attacks by 6.67% when compared to the control treatment of 46.67%. Meanwhile, fusarium wilt disease when given PGPR 450 ml/tan was 0.00% compared to the control treatment of 33.33%.